Dispositional beliefs regarding “affect as information” determine the perception of persuasive self-efficacy - Garcia-Marques, Teresa (2017)
In this paper, we approach the relationship between believing that affect informs about the validity of a claim and believing that one persuasive strategy will be more or less efficient in changing one’s own attitude. In one study, participants were asked to select from a set of features of a persuasive context those they perceived to have more persuasive power. Results showed that these selections were clearly clustered in two groups, suggesting that individuals tend to select either more cognitive features or more experiential affective features. Individual measures regarding participants’ need for cognition and faith in intuition did not explain the tendency to select more one type of cluster or another, but this selection was determined by how much people generally believe that affect informs about the validity or goodness of a claim.